Regular and Irregular Use and Reasons for Discontinuation of Solifenacin Therapy in Patients with Overactive Bladder Managed by Urologists - Mateusz Małkowski; Agnieszka Almgren-Rachtan; Magdalena Olszanecka-Glinianowicz; Jerzy Chudek; Piotr Chłosta (Pharmaceuticals, 2024)
Solifenacin, a selective muscarinic receptor antagonist, is one of the best-tolerated and most effective medicines that relieve storage symptoms in patients with an overactive bladder (OAB). However, the persistence of solifenacin in daily clinical practice remains far below that reported in clinical trials. This study aimed to analyze the adherence of patients to the therapy and the reasons for solifenacin discontinuation and non-regular use in OAB patients managed by urologists. Data concerning non-compliance and the discontinuation of solifenacin, along with the reasons, were collected during two consecutive visits for 64,049 OAB outpatients. Over the two visits, 81.6% of the patients continued therapy, and 88.6% were taking solifenacin regularly. An age ≥ 75 yrs., the male sex, a rural or small-city dwelling, and a prescription of ≥10 mg predicted therapy continuation. The female sex, a higher education, a short or long duration of an OAB, and a non-idiopathic OAB predicted regular use. The persistence of nycturia and urinary incontinence during therapy predicted both discontinuation and non-regular use. Dissatisfaction with therapy was the most frequent reason for discontinuation. In conclusion, an initial prescription of solifenacin at a low dose reduces the chance of OAB symptom improvement and results in more frequent discontinuation. A high rate of discontinuation related to dissatisfaction suggests unrealistic expectations for OAB patients and insufficient education by urologists.